Ability to Cope with Pain Puts Migraine Surgery Patients in Perspective. Issue 1 (January 2018) - Gfrerer, Lisa; Lans, Jonathan; Faulkner, Heather R.; Nota, Sjoerd; Bot, Arjan G. J.; Austen, William Gerald
Abstract : Background: Candidates for migraine surgery are chronic pain patients with significant disability. Currently, migraine-specific questionnaires are used to evaluate these patients. Analysis tools widely used in evaluation of better understood pain conditions are not typically applied. This is the first study to include a commonly used pain questionnaire, the Pain Self-Efficacy Questionnaire (PSEQ) that is used to determine patients' pain coping abilities and function. It is an important predictor of pain intensity/disability in patients with musculoskeletal pain, as low scores have been associated with poor outcome. Methods: Ninety patients were enrolled prospectively and completed the Migraine Headache Index and PSEQ preoperatively and at 12 months postoperatively. Scores were evaluated using paired t tests and Pearson correlation. Representative PSEQ scores for other pain conditions were chosen for score comparison. Results: All scores improved significantly from baseline ( p < 0.01). Mean preoperative pain coping score (PSEQ) was 18.2 ± 11.7, which is extremely poor compared with scores reported for other pain conditions. Improvement of PSEQ score after migraine surgery was higher than seen in other pain conditions after treatment (112 percent). Preoperative PSEQ scores did not influence postoperative outcome. Conclusions: The PSEQ successfully demonstrates the extent of debility in migraine surgery patients by putting migraine pain in perspective with other known pain conditions. It further evaluates functional status, rather than improvement in migraine characteristics, which significantly adds to our understanding of outcome. Poor preoperative PSEQ scores do not influence outcome and should not be used to determine eligibility for migraine surgery. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.